The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/andp.201500211
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic neutrinos in laboratory experiments and astrophysics

Abstract: An overview of neutrino electromagnetic properties, which open a door to the new physics beyond the Standard Model, is given. The effects of neutrino electromagnetic interactions both in terrestrial experiments and in astrophysical environments are discussed. The experimental bounds on neutrino electromagnetic characteristics are summarized. Future astrophysical probes of electromagnetic neutrinos are outlined.Comment: 18 pages, 2 figures, Revised version, Annalen der Physik [Ann. Phys. (Berlin)] in press. a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 207 publications
(342 reference statements)
0
94
0
Order By: Relevance
“…[4][5][6]. In this section we briefly outline the general form of the electromagnetic interactions of Dirac and Majorana neutrinos.…”
Section: Electromagnetic Interactions Of Massive Neutrinosmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6]. In this section we briefly outline the general form of the electromagnetic interactions of Dirac and Majorana neutrinos.…”
Section: Electromagnetic Interactions Of Massive Neutrinosmentioning
confidence: 99%
“…[23]. In the case of millicharged massive neutrinos, electromagnetic gauge invariance implies that the diagonal electric charges e jj (j = 1, 2, 3) are equal [6]. It should be mentioned that the most stringent experimental constraints on the electric charge of the neutrino can be obtained from the neutrality of matter.…”
Section: Electromagnetic Interactions Of Massive Neutrinosmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that even tine values of the Majorana neutrino transition moments would probably be tested in future high-precision experiments with the astrophysical neutrinos. In particular, observations of supernova fluxes in the JUNO experiment (see [27][28][29]) may reveal the effect of collective spin-flavour oscillations due to the Majorana neutrino transition moment µ M ν ∼ 10 −21 µ B . There are indeed other new possibilities for neutrino magnetic moment visualization in extreme astrophysical environments considered recently [30,31].…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…We have to take into account the naturalness condition on the squared mass difference ∆m 2 η = m 2 η 1 − m 2 η 2 , emerging from radiative corrections after symmetry breaking [29]: 10) where M V is the mass of the vector boson associated with the SU(2) ν symmetry breaking and α W is the electroweak fine-structure constant. Taking the experimental limits on the SU(3) L gauge boson masses [39] into consideration we set M V ∼ m η ∼ 5 TeV and get ∆m 2 η 7 · 10 5 GeV 2 .…”
Section: Voloshin-type Symmetrymentioning
confidence: 99%